FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN POSBINDU PTM DI PUSKESMAS ROWOSARI KOTA SEMARANG - Antono Suryoputro; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Posbindu PTM becomes a government strategy through promotion and prevention, as well as reducing the risk factors of PTM through empowering communities with a target age of 15 years and over. In 2017 Rowosari Health Center had the highest number of PTM cases in Semarang City with 5,469 cases but the visit coverage of Posbindu PTM is only 18% of the total registered participants. This study uses a cross sectional design and uses a questionnaire to a sample of 84 respondents. The results showed a low utilization, where 81% of respondents did not use Posbindu PTM. The results of the relationship test using chi square showed p value <0.05 between the variables of perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, and cues (family, peers, cadres, and health workers support) with the utilization of Posbindu PTM. Whereas the respondent characteristic variables (age, gender, education, employment status, and knowledge) in this study were not related to the utilization of Posbindu PTM. So the conclusions is there are relationship between perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, family supports, peers supports, cadres supports, and health workers support with the utilization of Posbindu PTM in in the work area of Rowosari Health Center. Suggestions in this study are through the role of cadres, peers and families inviting each other to come together to Posbindu PTM.